Molecular T2 asthma phenotypes are stable but heterogeneous: the usefulness of periostin for endotyping - Bobolea, Irina; Guillén-Vera, Daniela; De las Cuevas-Moreno, Natividad; García-Granero, Diego Blanco; Loli-Ausejo, David; Melero-Moreno, Carlos (Frontiers in Allergy, 2023)
Background The stability of molecular T2/non-T2 phenotypes remains uncertain. The objectives of this study were to assess the stability of these phenotypes and the correlation between serum periostin and asthma T2 phenotypes and endotypes. Methods Demographics, clinical data, and blood samples were collected. Patients diagnosed with moderate-to-severe asthma were classified into T2 or non-T2 according to previously defined thresholds of blood eosinophilia and serum total IgE levels. Asthma endotype was also determined. After at least 1 year of follow-up, the stability of T2 phenotypes and endotypes was assessed. Results A total of 53 patients (72% women), mean age 47 years (range 16–77), were included. In the initial and second evaluations, the T2 phenotype was found in 41.5% and 43.4% of patients and the non-T2 phenotype was found in 58.4% and 56.7%, respectively. The mean [standard deviation (SD), range] serum periostin level was 52.7 (26.2, 22.6–129.7) ng/mL in patients with T2 phenotype, and 39.3 (25.6, 7.7–104.) ng/mL in non-T2 patients (P = 0.063). Periostin levels correlated to endotypes (P = 0.001): 45.7 (27.9) ng/mL in allergic asthma (n = 16 patients), 64.7 (24.9) in aspirin-exacerbated respiratory disease (n = 14), 59.0 (27.6) ng/mL in late-onset eosinophilic asthma (n = 4), and 28.3 (13.3) ng/mL in non-eosinophilic asthma (n = 18). Conclusions T2 and non-T2 asthma phenotypes assessed by accessible methods in daily practice are stable over time yet widely heterogeneous. Serum periostin does not discriminate between T2 and non-T2 phenotypes. Nevertheless, its correlation to asthma endotypes may contribute to guide therapies targeting T2 cytokines in a more personalized approach.